Institutions in the Economic Fitness Landscape: What Impact Do Welfare State Institutions Have on Economic Performance? - Ronald Schettkat (Institute for the Study of Labor (IZA), 2003)
This paper uses data from 20 OECD countries to investigate the impact of welfare state institutions (especially employment protection, wage bargaining and work incentives) on the functioning of the labour market both theoretically and empirically. It shows that the impact of welfare state institutions is not as clear-cut as the deregulationists' view suggests. This result may be surprising against the background of the common view that welfare state measures cause European employment problems but it is in line with the outcomes of many other economic studies. The reasons for the ambiguous effects of welfare state institutions are manifold but the most important reason is the complexity of the impacts. There are many side-effects or second-round effects of welfare state institutions which, although often neglected, prove to be very important in the real ?imperfect market? world. Many welfare state institutions only have a clear-cut negative effect against the background of the theoretical perfect market model.
Keywords: P5; E2; J0; P1; 330; welfare states; institutions; economic performance; growth; employment; Sozialstaat; Institutionalismus; Wirtschaftswachstum; Beschäftigungseffekt; Arbeitsmarktflexibilisierung; Kündigungsschutz; Tarifpolitik; Lohnstruktur; OECD-Staaten